The Antidepressant Amitriptyline is a TrkA and TrkB Receptor Agonist that Promotes TrkA/TrkB Heterodimerization and Has Potent Neurotrophic Activity - Jang, Sung-Wuk (2009)
Neurotrophins, the cognate ligands for the Trk receptors, are homodimers and induce Trk dimerization through a symmetric bivalent mechanism. We report here that amitriptyline, an antidepressant drug, directly binds TrkA and TrkB and triggers their dimerization and activation. Amitriptyline, but not any other tricyclic or SSRI antidepressants, promotes TrkA autophosphorylation in primary neurons and induces neurite outgrowth in PC12 cells. Amitriptyline binds the extracellular domain of both TrkA and TrkB and promotes TrkA-TrkB receptor heterodimerization. Truncation of amitriptyline binding motif on TrkA abrogates the receptor dimerization by amitriptyline. Administration of amitriptyline to mice activates both receptors and significantly reduces kainic acid-triggered neuronal cell death. Inhibition of TrkA, but not TrkB, abolishes amitriptyline's neuroprotective effect without impairing its antidepressant activity. Thus, amitriptyline acts as a TrkA and TrkB agonist, and possesses marked neurotrophic activity.